Records of the Australian Federation of Consumer Organizations - Australian Federation of Consumer Organizations (1979)
The records in MS 8352 comprise general subject files, product files and correspondence and other records in subject groupings (53 boxes, 1 phase box).
The MS Acc GB 1993.1509A instalment consists of further Australian Federation of Consumer Organizations files (25 boxes, 1 carton).
The Acc98.208 instalment comprises minutes of Council, Executive and annual general meetings, submissions, speeches, media releases, financial statements, strategic plans, mail-outs, Ralph Nader video, publications and "History of Australian consumer movement" (12 cartons).
The Acc98.221 instalment includes policy papers, submissions, minutes, member lists, annual returns and topical files (1 carton).
Manuscript reference no.: MS 8352, MS Acc GB 1993.1509A, MS Acc98.208, MS Acc98.221.
The Australian Federation of Consumer Organizations (AFCO) is an independent, non-governmental organization which was founded in 1974 as the peak body of the consumer movement in Australia. The functions of AFCO are to represent the views of member bodies and consumers generally to the government, industry and the professions, and to liaise between the elements of the consumer movement. The national headquarters of AFCO closed in August 1998.
Finding aid available in the Special Collections Reading Room and on the Internet at: http://www.nla.gov.au/ms/findaids/8352.html
Keywords: Australian Federation of Consumer Organizations -- Archives; Consumer panels -- Australia -- Archives; Consumers -- Australia; Consumer protection -- Australia; Consumer protection -- Australia -- Citizen participation; Consumer education -- Australia